2012
DOI: 10.1007/s10483-012-1553-8
|View full text |Cite
|
Sign up to set email alerts
|

Importance of aging to dehydration shrinkage of human dentin

Abstract: There is an increase in the mineral content of human dentin with aging. Due to the consequent changes in the mineral to the collagen ratio, this process may influence the degree of hydrogen bonding that occurs with the loss of water and the extent of shrinkage as a result of dehydration. Thus, the objective of this investigation is to quantify the differences in the dehydration shrinkage of human dentin with patient age. Specimens of coronal dentin are prepared from the molars of young (23 age 34) and old (52 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…33,34 Due to the consequent changes in the mineral to the collagen ratio, this process may influence the degree of hydrogen bonding that occurs with the loss of water and the shrinkage extent as a result of dehydration. Wang et al 35 studied the aging importance to dehydration shrinkage of human dentin and found that the degree of anisotropy in the shrinkage increases from the pulp to the EDJ and is the largest in the young dentin (23 age 34). Another age change was an increase in dead tracts within dentin.…”
Section: Resultsmentioning
confidence: 99%
“…33,34 Due to the consequent changes in the mineral to the collagen ratio, this process may influence the degree of hydrogen bonding that occurs with the loss of water and the shrinkage extent as a result of dehydration. Wang et al 35 studied the aging importance to dehydration shrinkage of human dentin and found that the degree of anisotropy in the shrinkage increases from the pulp to the EDJ and is the largest in the young dentin (23 age 34). Another age change was an increase in dead tracts within dentin.…”
Section: Resultsmentioning
confidence: 99%
“…The development and application of noncontact methods for precise displacement measurement technique is of substantial interest for engineers. [25][26][27][28] For biomedical applications, there are often additional technical challenges to overcome that must be considered. This study has illustrated the use of DIC as an optical approach for accurately quantifying the movement of bones in the treatment of pes planus and distal tibiofibular syndesmosis injury.…”
Section: Discussionmentioning
confidence: 99%
“…As this technique is a post analysis method on fragments, it cannot be used to track the crack growth while loading. Previous studies have shown that digital image correlation (DIC) could be used to identify deformation and crack growth in sliced tooth‐like specimens, compare strain distributions within the surrounding bone of implant‐supported crowns, and measure the dehydration shrinkage of dental materials and polymerization shrinkage of light‐cured dental composites . The combination of these two methods could help our understanding of the fracture mechanism of dental materials.…”
mentioning
confidence: 99%